Attractant potential of Enterobacter cloacae and its metabolites to Bactrocera dorsalis (Hendel) - Duan, Yawen; Li, Anjuan; Zhang, Lin; Yin, Chongwen; Li, Zhihong; Liu, Lijun (Frontiers in Physiology, 2024)
Objective: Bactrocera dorsalis (Hendel) has a wide host range. It has been the most important quarantine pest in many countries or regions. Currently, chemical control and bait trapping are mainly used in the monitoring and prevention and control of B. dorsalis. However, chemical control will cause pollution to the environment and cause drug resistance of insects. Methyl eugenol, the main attractant currently used, can only attract males of B. dorsalis.Method: This study focused on the attractant function and active substances of one key intestinal bacterium, Enterobacter cloacae, which was isolated from B. dorsalis.Results: First, the attraction of the E. cloacae autoclaved supernatant to male and female adults of 0, 6, and 15 days post-emergence was confirmed using a Y-type olfactometer. Subsequently, through metabolome sequencing and bioassays, L-Prolinamide was identified and confirmed as the most effective attractant for B. dorsalis. Finally, the synergistic effect of L-Prolinamide with the sex attractant ME was validated through field experiments. This study confirmed the attraction effect of E. cloacae on B. dorsalis, and also proved the attraction effect of L-Prolinamide, the metabolite of E. cloacae, on B. dorsalis. This laid a theoretical foundation for the development of new attractant and safe, green, and efficient prevention and control technology of B. dorsalis. Fed by the larvae (themselves) yes no no no Fed by the larvae (other than themselves) no yes no no